Evaluation of legume shrubs improved fallow for abandoned agricultural land rehabilitation (International Journal of Agricultural Research, Innovation and Technology, 2020)
The experiment was conducted on abandoned agricultural land at Bena-Tsemay District, Southern Ethiopia. It was designed to evaluate legume shrubs growth performance, and its potential for soil fertility enhancement through improved fallow practice. The results of the current study showed that the growth performance of legume species reveals variation in different growth parameters. The mean height of Sesbania sesban was significantly higher than the other species except for Senna siamea. Senna siamea recorded the highest mean stem diameter followed by Sesbania sesban, 3.47 cm, and 2.86 cm, respectively. Legume shrub species for soil fertility enhancement under improved fallow showed an increase in soil pH, organic carbon, organic matter, phosphorus level, available potassium, and total nitrogen during the growth period. Sesbania provides a large amount of nitrogen (2.91 t ha- 1) within two years fallow period, linked with the carbon to nitrogen ratio (11.22) having better mineralization potential. The growing of promising legume shrub species as an improved fallow practice has an important contribution in the restoration process of abandoned agricultural land and used as an option to grow crops in a rotational cropping system.Int. J. Agril. Res. Innov. Tech. 10(1): 64-70, June 2020